Feasibility Study: Kapah Clam (Meretrix lyrata) Consumption Based on the Amount of Heavy Metal Lead (Pb) in Pulau Labu, Deli Serdang Regency - Sinuraya, Sofyanurrazaq; Mukhlis; Delvian (TALENTA Publisher, Universitas Sumatera Utara, 2023)
The hazardous heavy metal lead (Pb) can infiltrate the human body through the food chain. This study aimed to determine the maximum allowed amount of lead (Pb) and the lead heavy metal content in the meat of kapah clams (Meretrix lyrata) from Pantai Labu, Deli Serdang Regency, North Sumatra Province. This study used stratified random sampling in three locations: Bagan Beach, Muara Serdang, and Putra Deli. Heavy metal lead (Pb) measurements were conducted using the Parkin Elmer Atomic Absorption Spectrophotometry (AAS) method with an Atomic Absorption Spectrophotometer. Maximum Tolerable Intake (MTI) or Maximum Weekly Intake (MWI) is divided by the amount of heavy metal lead (Pb) in Kapah Clam meat (Meretrix lyrata) to determine the permissible consumption limit. As a result, exceeding the MTI limit can lead to toxicity.